Synthesis and Characterization of Single Crystal of bis-(L-Histidinato)nickel(II) Monohydrate - Hashemian, Saeedeh (Asian Journal of Chemistry, 2012)
The complex bis-(L-histidinato)nickel(II) monohydrate has been synthesized and structurally characterized by single-crystal X-ray diffraction. This complex was solved in the monoclinic system, space group C2, with the following unit-cell parameters: a = 29.313(6) Å, b = 8.227 (2)Å, c = 6.264(1) Å, a = 90º, b = 90.189(5)º, g = 90º, Z = 4, V= 1510.5(5)ºA3. The final R value was R1 = 0.0301 for 7558 measured reflections.